Genome-Wide Association Study of Metachronous Colorectal Adenoma Risk among Participants in the Selenium Trial. (13th December 2022) - Trejo, Mario Jesus; Batai, Ken; Chen, Yuliang; Brezina, Stefanie; Chow, H-H Sherry; Ellis, Nathan; Lance, Peter; Hsu, Chiu-Hsieh; Pogreba-Brown, Kristen; Bishop, Maria; Gsur, Andrea; Jacobs, Elizabeth T.
Abstract: Genetic variants related to colorectal adenoma may help identify those who are at highest risk of colorectal cancer development or illuminate potential chemopreventive strategies. The purpose of this genome-wide association study was to identify genetic variants that are associated with risk of developing a metachronous colorectal adenoma among 1, 215 study participants of European descent from the Selenium Trial. Associations of variants were assessed with logistic regression analyses and validated in an independent case-control study population of 1, 491 participants from the Colorectal Cancer Study of Austria (CORSA). No statistically significant genome-wide associations between any variant and metachronous adenoma were identified after correction for multiple comparisons. However, an intron variant of FAT3 gene, rs61901554, showed a suggestive association ( P  = 1.10 × 10 −6 ) and was associated with advanced adenomas in CORSA ( P  = 0.04). Two intronic variants, rs12728998 and rs6699944 in NLRP3 were also observed to have suggestive associations with metachronous lesions ( P  = 2.00 × 10 −6 ) in the Selenium Trial and were associated with advanced adenoma in CORSA ( P  = 0.03). Our results provide new areas of investigation for the genetic basis of the development of metachronous colorectal adenoma and support a role for FAT3 involvement in the Wnt/β-catenin pathway leading to colorectal neoplasia. Trial Registration number: NCT00078897 (ClinicalTrials.gov).